RELEVANSI PEMIKIRAN AL-GHAZALI TERHADAP TANTANGAN SEKULARISME DALAM PENDIDIKAN ISLAM MODERN - Tahira, Kayla Nurul; Putri, Dinda Nauli; Shodri, Wridan Fauzi Rahman; Qolbiyah, Aini; Parhan, Muhamad (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2025)
This article discusses the relevance of Al-Ghazali’s thought in addressing the challenges of secularism in modern Islamic education. The main problem explored is how secularism, which separates religious values from the educational system, can weaken the character and spirituality of Muslim students. This study employs a qualitative approach through literature review of Al-Ghazali’s works and related Islamic educational literature. The findings indicate that Al-Ghazali emphasizes the integration of knowledge and spiritual values, so that education is not only oriented toward intellectual achievement but also moral and ethical development. The proposed solution is the implementation of Al-Ghazali’s holistic educational concept, which balances aqli (rational) and naqli (revealed) sciences. The main finding of this article confirms that Al-Ghazali’s thought is highly relevant for overcoming the dichotomy between religious and secular sciences caused by secularism, and for strengthening Islamic identity in the era of globalization. The conclusion of this study highlights the importance of revitalizing the role of teachers and developing an integrative curriculum based on Islamic values to build a high-quality and competitive Islamic education. Abstrak Artikel ini membahas relevansi pemikiran Al-Ghazali dalam menghadapi tantangan sekularisme pada pendidikan Islam modern. Permasalahan utama yang diangkat adalah bagaimana sekularisme, yang memisahkan nilai agama dari sistem pendidikan, dapat melemahkan pembentukan karakter dan spiritualitas peserta didik Muslim. Penelitian ini menggunakan pendekatan kualitatif dengan studi pustaka terhadap karya-karya Al-Ghazali dan literatur terkait pendidikan Islam. Hasil kajian menunjukkan bahwa Al-Ghazali menekankan pentingnya integrasi antara ilmu pengetahuan dan nilai-nilai spiritual, sehingga pendidikan tidak hanya berorientasi pada kecerdasan intelektual, tetapi juga pembentukan moral dan akhlak. Solusi yang diusulkan adalah penerapan konsep pendidikan menurut Al-Ghazali, yang menggabungkan ilmu aqli dan naqli secara seimbang. Temuan utama artikel ini menegaskan bahwa pemikiran Al-Ghazali sangat relevan untuk mengatasi dikotomi antara ilmu agama dan ilmu umum akibat sekularisme, serta memperkuat identitas keislaman di era globalisasi. Simpulan dari kajian ini adalah perlunya revitalisasi peran guru dan pengembangan kurikulum integratif berbasis nilai-nilai Islam untuk membangun pendidikan Islam yang berkualitas dan berdaya saing.